2016
DOI: 10.1111/joca.12123
|View full text |Cite
|
Sign up to set email alerts
|

Who Feels Credit Constrained in Europe? The Role of Social Capital

Abstract: This paper analyzes the influence of social capital in consumers' perceptions of their borrowing constraints, which affect numerous financial decisions. Social capital is a multidimensional concept that concerns consumers' ability to obtain benefits from their engagement in social activities and social networks. To test the hypotheses, we rely on data from the European Social Survey. The results indicate that the four indicators of social capital (bonding capital, bridging capital, trust in people, and trust i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Furthermore, prior literature indicated that people with similar economic backgrounds were more likely found in the same social network, which would utilize social capital to benefit themselves for a better financial outcome. Thus, in an investment context, income may serve as a mediator in a positive relationship between the social network and investment decisions (Pereira et al, 2017). Our findings confirmed that this association was mediated through income levels significantly (H2), as demonstrated in the decomposition analysis.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, prior literature indicated that people with similar economic backgrounds were more likely found in the same social network, which would utilize social capital to benefit themselves for a better financial outcome. Thus, in an investment context, income may serve as a mediator in a positive relationship between the social network and investment decisions (Pereira et al, 2017). Our findings confirmed that this association was mediated through income levels significantly (H2), as demonstrated in the decomposition analysis.…”
Section: Discussionsupporting
confidence: 83%
“…In the opposite direction, we include a variable measuring self-perceived discrimination. The proxies for social capital used are in line with other studies based on ESS data [12,[42][43][44]. We further consider interaction variables between the covariates male and informal network/civic engagement.…”
Section: Data and Variablesmentioning
confidence: 99%
“…data set and a different methodological approach [9]. Social capital is a multidimensional concept, related with participation in social networks and trust in people or institutions, which has been increasingly used in economic analyses [10][11][12]. A strong association between social capital and health has already been established [13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Understanding how these financial problems affect consumers is crucial to design financial services that respond to their needs. Especially when consumers are feeling credit constrained (Pereira, Coelho, & Lourenço, 2017) or lack of financial literacy, they are in need of financial advice (Gerrans & Hershey, 2017). Research also focuses on understanding how financially literate are women (Bucher-Koenen, Lusardi, Alessie, & van Rooji, 2017) and how parents' financial behavior affects their children's financial behavior (Tang, 2017).…”
Section: Interpretive Consumer Behavior Researchmentioning
confidence: 99%